Do motivation and perceptions of equality and discrimination in Physical Education impact physical activity in secondary education students? A sex-based analysis - Dilan Galeano-Rojas; Claudio Farías-Valenzuela; Claudio Hinojosa-Torres; Pedro Valdivia-Moral (Revista Española de Pedagogía, 2025)
The benefits of physical activity in the school setting are widely proven; however, factors such as student motivation and equality perceptions are determinants of participation and learning opportunities in Physical Education. The aim of the present research was to analyse existing relationships between physical activity, motivation and perceptions of equality and discrimination in Physical Education as a function of sex, as well as to identify the extent to which motivation and equality affect physical activity engagement in secondary education students. The sample was made up of 310 students (13.9 ± 1.2 years) with the PAQ-C, the motivation in Physical Education questionnaire and the questionnaire of perception of equality and discrimination in Physical Education being administered for data collection. Data were analysed according to Mann-Whitney U, Spearman correlation and linear regression outcomes. Main outcomes demonstrate statistically significant sex differences in physical activity engagement and perceptions of equality and discrimination. In turn, physical activity engagement was observed to be positively associated with intrinsic and extrinsic motivation (identified, introjected and external regulation). Further, perceived equality was related with self-determined forms of motivation, whilst perceived discrimination was related with less self-determined forms of motivation. Finally, regression outcomes revealed that identified regulation positively and significantly predicts physical activity engagement, whilst perceived equality was inversely related with this variable. In conclusion, males present higher levels of physical activity engagement, lower perceptions of equality and higher perceptions of discrimination. Furthermore, more self-determined levels of motivation contribute towards higher levels of physical activity engagement in the context of Physical Education.